2016
DOI: 10.1016/j.renene.2015.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparative testing of energy yields from micro-algal biomass cultures processed via anaerobic digestion

Abstract: . Comparative testing of energy yields from microalgal biomass cultures processed via anaerobic digestion. Renewable Energy, 87,[744][745][746][747][748][749][750][751][752][753] http://www.sciencedirect.com/science/article/pii/S0960148115304286 doi:10.1016/j.renene.2015.11.009 __________________________________________________________________________________ Comparative testing of energy yields from micro-algal biomass cultures processed via anaerobic digestion Keiron P. Roberts, Sonia Heaven, Charles J. Bank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 49 publications
1
28
1
Order By: Relevance
“…In turn, the yield of methane production from the microalgae biomass may reach 240-307 mL/g VS for Chlorella vulgaris and 210-261 mL/g VS for Scenedesmus sp. (Ras et al 2011;Zamalloa et al 2012;Roberts et al 2016), which was similar to our findings of 315.71 mL/g VS for the substrate consisting of Chlorella sp. and Scenedesmus sp.…”
Section: Biogas/methane Production Rate and Yield From The Substratessupporting
confidence: 92%
“…In turn, the yield of methane production from the microalgae biomass may reach 240-307 mL/g VS for Chlorella vulgaris and 210-261 mL/g VS for Scenedesmus sp. (Ras et al 2011;Zamalloa et al 2012;Roberts et al 2016), which was similar to our findings of 315.71 mL/g VS for the substrate consisting of Chlorella sp. and Scenedesmus sp.…”
Section: Biogas/methane Production Rate and Yield From The Substratessupporting
confidence: 92%
“…TAN, FAN total VFA and pH in R1-R4 during the experimental period are shown in Fig This long-term TAN accumulation in the digesters is attributable to the high-nitrogen feedstock combined with low rates of conversion of nitrogen into biomass and limited losses into the gas phase as NH 3 . It is recognised, however, that multiple factors affect the final TAN concentration in a digester (Lindorfer et al, 2012, Roberts et al, 2016 as well as its partitioning into the free and ionic forms. It is also likely that methanogens and other members of the anaerobic consortium can acclimate to ammonia, and it is therefore not surprising that inhibition of the digestion process has been reported over a wide range of TAN concentrations (Chen et al, 2008).…”
Section: Digestion Stability Parametersmentioning
confidence: 99%
“…This was equivalent to an estimated specific methane yield of 0.33 g·CH 4 ·g −1 of Volatile solids (VS) for algae with a 20% lipid content, corresponding to the higher end of the range for quoted methane yields [15,20,38]. Recent studies have found a 60% yield for Dunaliella salina [39] and 59%-79% yield for five commercially exploited microalgal species [40].…”
Section: Anaerobic Digestion Methane Yield and Heat Recoverymentioning
confidence: 99%